The Role of the Great Mosque of Binjai City in the Development of Da'wah History - Abdul Rahman; Muktarruddin; Emiya kampina; Rakhas Djuniardi; Sophia Lajuba (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This study is focused on the early process of the arrival of Islam in Binjai City and its development process. To find out the influential figures in the development of Islam in the city of Binjai, to find out the heritage buildings of the Binjai Islamic community and to find out the Islamic heritage that still exists today. This discussion was carried out with a historical approach using the Library Research method (library research method) and Field Research (field research method) by conducting interviews in addition to data collection by means of literature review. Data collection techniques were carried out by collecting documentation on the traces of Islam in Binjai City. . The results obtained from this research on the spread of Islam in the city of Binjai are inseparable from the large role in the spread of Islam from the Langkat Sultanate which is domiciled in Binjai City because Binjai was part of the Langkat sultanate before finally forming its own region. That the role of the leaders is very high in the process of Islamization through educational institutions as evidenced by the Islamic heritage in the City of Binjai in the form of mosques, tombs, Islamic schools and the work of the scholars.